Assessment of Genetic Diversity among Pigeon pea Male Sterile lines and Popular Cultivars using SSR Markers - SNCVL Pushpavalli; R. Raja Rajeswari and; C.V. Sameer Kumar (Electronic Journal of Plant Breeding, 2016)
In the present study genetic diversity studies have been carried out using twenty five SSR markers in a set of pigeonpea genotypes comprising of male sterile lines and popular cultivars. The primers amplified a total of 99 bands with highest PIC of 0.79. The SSR markers grouped the genotypes into four clusters based on UPGMA and Principal Component Analysis. The male sterile lines along with PRG158 were grouped into three clusters while, the remaining cultivars formed a distinct cluster indicating the narrow genetic base of released cultivars. PCA revealed that phenotypic variation explained by the SSRs ranged from 4.7% to 49.6% with PC1 and PC2 accounting for 49.6% and 30.8% of total variation. The study indicated the existence of diversity between the male sterile lines and the popular cultivars which can be exploited for hybrid breeding program.